Miasto – wyobrażenie – refrakcja. O niemieckości Gdańska w rosyjskim przekładzie Hanemanna Stefana Chwina - Kaźmierczak, Marta (Wydawnictwo Poznańskie Studia Polonistyczne i Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2014)
The article discusses representation of a third culture in translation: it compares the image of Gdańsk as a city with strong German cultural presence, presented in Stefan Chwin’s novel Hanemann, with the same image in Ksenia Starosielska’s Russian translation of the novel. The image of the old Danzig in Chwin’s work consists of linguistic allusions and references to German literature: interpolations, German proper names, realities from early decades of the 20th century, and the figure of Heinrich von Kleist. Some elements of language and notions in the novel could seem more distant for a R ussian reader than for a Polish one. The present author considers, thus, if and how reality and topography of the city have been presented to secondary receipients. The article focuses on the translator’s strategy of approach to a third culture, reflected both in translator’s choices in the main text, as well as the number and formulation of footnotes. Because images of places in text are also created by non-verbal means, the graphical paratexts are also interesting for the discussion. The transformations are discussed in terms of refraction, which leads to conclusions about the role of the analyzed translation in its target culture.
On Germanness of Gdańsk in the Russian translation of Stefan Chwin’s Hanemann
Keywords: translation; third culture; imagination; refraction; Gdańsk; German; Ksenia Starosielska